Corporate Governance and Stakeholders' Strategic Calculus as Organization's Competitive Advantage - Rafal KOZLOWSKI (Communications of International Proceedings, 2021)
The current debate in corporate governance is about the fundamental purpose of business, shareholder value maximization versus meeting stakeholder claims. Proponents of the value maximization principle say that a firm exists to maximize shareholder value and that managers cannot logically be expected to serve many masters at the same time as suggested by shareholder theory. Proponents of stakeholder theory, on the other hand, say that a firm exists to satisfy the claims of its all stakeholders. The theoretical framework of corporate governance process is proposed, where stakeholders’ activities and interactions with others play the main role. This paper applies the methodology of a multidimensional analysis to develop framework that defines the components of the key governance processes, particularly those relating to the dynamics between the board and its critical external and internal stakeholders.
Keywords: Stakeholders; Corporate Governance